EFEKTIVITAS DAN EFISIENSI DESIGN LAYOUT PADA KANTOR POLISI RESORT KOTA (POLRESTA) PEKANBARU - Indra Rochmadi Suhartono; Samsir Samsir; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is aimed to measure the employees’ working efficiency on the side of employees’ activities in a month. It is done by analyzing the first office layout and designing the alternative one for office of pekanbaru capital police. The analysis testing here is using descriptive and historical analysis. Furthermore, the first layout of the office has several weaknesses especially on the employees’ office room arrangement which is not well-arranged. This problem leads to the inefficiency and ineffectiveness of the office working system. Moreover, the distance between one room and another is also another problem. It also causes the employees not to work cooperatively and freely. This problem positively causes the room look not good and not interesting. After redesigning the room by having several alternative layouts, it can be concluded that one of the designs (the third design) has given a significant change of the look of the first office layout that leads to the efficiency and effectiveness of the employees’ activities which is decreasing to 9,545km in a month.Keywords : optimization, layout, efficiency, existing